Wandering through Endless Nothingness: Reading Fictional Mind in David Markson’s Wittgenstein’s Mistress - Maryam Rabti; Alireza Farahbakhsh (Cogent Arts & Humanities, 2023)
The present article attempts to investigate David Markson’s Wittgenstein’s Mistress through the lens of cognitive narratology. To understand “the whole mind” of Kate, the protagonist of the novel, this study endeavors to explore her intermental thoughts (interpersonal relationships), intramental thoughts (inner speech), and dispositions. The central questions of the present study are: How does Kate, the major female character of Wittgenstein’s Mistress reconstruct the minds of others in her own thought, and how does her mental state is manifested in her narration of episodic traumatic memories and qualia? And how does her internal world emerge from a combination of collective minds as far as Alan Palmer’s conception of “intermental thought” is concerned? Alan Palmer’s humanizing approach to postclassical narratology, which provides the theoretical backbone of the present research, underscores the mental interactions of fictional characters and explores actions, dispositions, and interpersonal relationships. The article concludes that Kate’s internal world is constructed out of a combination of collective minds and her “intermental thoughts.”